2021
DOI: 10.3390/cells10123458
|View full text |Cite
|
Sign up to set email alerts
|

HOPX Plays a Critical Role in Antiretroviral Drugs Induced Epigenetic Modification and Cardiac Hypertrophy

Abstract: People living with HIV (PLWH) have to take an antiretroviral therapy (ART) for life and show noncommunicable illnesses such as chronic inflammation, immune activation, and multiorgan dysregulation. Recent studies suggest that long-term use of ART induces comorbid conditions and is one of the leading causes of heart failure in PLWH. However, the molecular mechanism of antiretroviral drugs (ARVs) induced heart failure is unclear. To determine the mechanism of ARVs induced cardiac dysfunction, we performed global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“… 270 Trichostatin A and emodin have good clinical value in the treatment of cardiac hypertrophy and heart failure, through deacetylation of histone. 271 , 272 It was found that MPT0E014 generated beneficial impact in heart failure by inhibiting HDAC, increasing cardiac function, and alleviating the effects of heart failure on cardiometabolism and inflammation. 273 HDAC class I inhibitor Mocetinostat reverses myocardial fibrosis in heart failure by reducing myocardial fibroblast activation and inducing cell cycle arrest/apoptosis.…”
Section: Epigenetic Regulatory Mechanismsmentioning
confidence: 99%
“… 270 Trichostatin A and emodin have good clinical value in the treatment of cardiac hypertrophy and heart failure, through deacetylation of histone. 271 , 272 It was found that MPT0E014 generated beneficial impact in heart failure by inhibiting HDAC, increasing cardiac function, and alleviating the effects of heart failure on cardiometabolism and inflammation. 273 HDAC class I inhibitor Mocetinostat reverses myocardial fibrosis in heart failure by reducing myocardial fibroblast activation and inducing cell cycle arrest/apoptosis.…”
Section: Epigenetic Regulatory Mechanismsmentioning
confidence: 99%
“…The Hopx gene has been closely studied and found to be upregulated in cART-treated PLHIV and plays a key role with regards to cardiomyocyte hypertrophy. Kashyap et al (2021) ( Kashyap et al, 2021a ) has also shown in their studies with knockout mice that Hopx expression causes increased size in cardiomyocytes while knockout mice showed size reduction. Furthermore, the Hopx gene has been proposed to negatively impact proliferation and diferentiation of cardiomyocytes ( Chen et al, 2002 ).…”
Section: Introductionmentioning
confidence: 96%
“…The exact mechanisms by which cART leads to heart dysfunction and toxicity at the cellular level have not been elucidated. However, studies have been able to show that cART treatment leads to oxidative stress, cellular hypertrophy, and modified histones in cardiomyocytes ( Kashyap et al, 2021a ; Kashyap et al, 2021b ). In addition, RNA-seq data analysis has demonstrated that differences in gene expression causes changes at the transcriptional level ultimately causing cardiac hypertrophy and toxicity ( Kashyap et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations